2019
DOI: 10.1021/acsnano.9b07499
|View full text |Cite
|
Sign up to set email alerts
|

PIEZO1-Mediated Currents Are Modulated by Substrate Mechanics

Abstract: PIEZO1 is a bona fide mammalian mechanically activated channel that has recently been shown to provide instructive cues during neuronal specification, texture sensing, and cell migration where mechanical inputs arise at the interface between the cells and their substrate. Here, we have investigated whether the mechanical properties of the substrate alone can modulate PIEZO1 activity, in response to exogenously applied stimuli, using elastomeric pillar arrays as force transducers. This methodology enables appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 60 publications
2
55
0
Order By: Relevance
“…The fact that stretch-dependent Ca 2+ accumulation is blocked by calpain inhibition further indicates that Piezo1 contributes to initial Ca 2+ release but calpain cleavage enables the higher levels of Ca 2+ entry that drive apoptosis 26 . Although Piezo1 appears in many different mechanical functions, the activation mechanism of Piezo1 is complex and both contributions from membrane tension and interaction with cytoskeletal proteins may modulate its activity 39,43 .…”
Section: Discussionmentioning
confidence: 99%
“…The fact that stretch-dependent Ca 2+ accumulation is blocked by calpain inhibition further indicates that Piezo1 contributes to initial Ca 2+ release but calpain cleavage enables the higher levels of Ca 2+ entry that drive apoptosis 26 . Although Piezo1 appears in many different mechanical functions, the activation mechanism of Piezo1 is complex and both contributions from membrane tension and interaction with cytoskeletal proteins may modulate its activity 39,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the activity of the downstream signaling pathways that govern the microgravity-induced cytoskeletal changes are significantly impaired and are at least in part due to the microgravitytriggered inhibition of FAK and/or RhoA signaling (Higashibata et al, 2006;Li et al, 2009;Tan et al, 2018). Furthermore, recent data suggest that changes to the cytoskeleton may also impact signaling via mechanically activated ion channels and contacts in response to both cell-generated (Nourse and Pathak, 2017;Ellefsen et al, 2019) and externally applied mechanical inputs (Bavi et al, 2019). Thus, downstream signaling of the numerous mechanotransduction pathways depend on the concerted interaction of the cytoskeleton, cell adhesion molecules, and force sensing proteins, including mechanically activated ion channels.…”
Section: The Impact Of Microgravity Of Cell Cytoskeletonmentioning
confidence: 99%
“…However, it should be noted that Piezo1 responsiveness to cyclic-stretch appears to be cell type-specific [ 34 ]. Substrate stiffness can also modulate Piezo1 activity in vitro; an increase in substrate stiffness reduced Piezo1 channel activation in HEK 293T cells transiently transfected with human Piezo1 [ 215 ]. Conversely, a reduction in the density of contact points between a cell and the external substrate, represented as roughness of the substrate, increased Piezo1 channel activity in HEK 293T cells expressing human Piezo1 [ 215 ].…”
Section: Piezo1 Channelmentioning
confidence: 99%
“…Substrate stiffness can also modulate Piezo1 activity in vitro; an increase in substrate stiffness reduced Piezo1 channel activation in HEK 293T cells transiently transfected with human Piezo1 [ 215 ]. Conversely, a reduction in the density of contact points between a cell and the external substrate, represented as roughness of the substrate, increased Piezo1 channel activity in HEK 293T cells expressing human Piezo1 [ 215 ]. Bavi and colleagues suggested that the responsiveness of Piezo1 to substrate stiffness and roughness indicates a synergistic mechanism between force sensed by the phospholipids and the actin cytoskeleton in HEK 293T cells expressing human Piezo1 [ 215 ], a concept further supported by evidence that Piezo1 acts as a novel component of integrin-based adhesions [ 34 ].…”
Section: Piezo1 Channelmentioning
confidence: 99%
See 1 more Smart Citation